2022
DOI: 10.3389/frobt.2022.983955
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mixed-cultural speech on the stereotypical perception of a virtual robot

Abstract: Despite the fact that mixed-cultural backgrounds become of increasing importance in our daily life, the representation of multiple cultural backgrounds in one entity is still rare in socially interactive agents (SIAs). This paper’s contribution is twofold. First, it provides a survey of research on mixed-cultured SIAs. Second, it presents a study investigating how mixed-cultural speech (in this case, non-native accent) influences how a virtual robot is perceived in terms of personality, warmth, competence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Participants preferred a voice with an accent matching their own when reading out tourist information about both the Swedish and American destinations. Although the results appear to contradict those on Singaporean Chinese by Batsaikhan et al (2021) and German-accented English by Obremski et al (2022), the comparison is complicated by the differing scenarios. A more direct comparison can be found in work by Niculescu et al (2008), who compared Singaporean English speakers' impressions of a Singaporean English-accented virtual help desk assistant to one with a British English accent.…”
Section: Accentcontrasting
confidence: 60%
See 3 more Smart Citations
“…Participants preferred a voice with an accent matching their own when reading out tourist information about both the Swedish and American destinations. Although the results appear to contradict those on Singaporean Chinese by Batsaikhan et al (2021) and German-accented English by Obremski et al (2022), the comparison is complicated by the differing scenarios. A more direct comparison can be found in work by Niculescu et al (2008), who compared Singaporean English speakers' impressions of a Singaporean English-accented virtual help desk assistant to one with a British English accent.…”
Section: Accentcontrasting
confidence: 60%
“…Given the stronger influence of accents on perception of individuals' cultural categorization (Rakić et al, 2011), this may have prompted a more critical evaluation of the robot in terms of competence. As described in section 3.1, negative impressions when there is alignment to one's accent (Niculescu et al, 2008;Batsaikhan et al, 2021;Obremski et al, 2022) or dialect (Torre and Maguer, 2020) have been reported in previous work.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations